I will be the silence, I will be in the silence: the great murmur as enunciative subjectivity in Beckett’s The unnamable - Matti, Felipe Andrés (Escritura e Imagen, 2024)
In this work it will be analyzed the collective enunciation that Gilles Deleuze and Félix Guattari formulate in Capitalism and schizophrenia. To do so, Samuel Beckett’s The unnamable will be taken as an example, given that not only Guattari directly refers to it in the preparative texts for The Anti-Oedipus, but also that the Beckettian essay is itself an enunciative formation that sheds light on the notions of the great murmur and being-language. Thus, as main hypothesis it is held that the language’s desterritorialization, process from which an enunciative formation that prescinds of the subject, would find support in the Beckettian writings. Also, as secondary hypothesis it is upheld that the assemblage of a deterritorialized language would sustain resemblances with the reflexive motion that suffers the grammatical subject that transverses the text and that peaks in its annihilation in favor of the silence, which would be the enunciative formation that refers to the great murmur that possibilities language.